The relationship between the critical biography of the Holy Prophet (PBUH) and the ideology of political Islam in the Indian subcontinent (Case study: Abul-A'la Maududi's opinions) - Yousof Heydarnezhad (تاریخ نگری و تاریخ نگاری, 2023)
At the beginning of the 20th century, the scholarly community of the Indian subcontinent witnessed the formation of a new type of biography of the Holy Prophet (peace be upon him). From the advent of Islam to the 20th century, biographies written in the Indian subcontinent had elements of descriptive and narrative historiography. With the emergence of Islamist political parties and movements, their attention to the biography of the Holy Prophet (PBUH) led to the creation of a new style in this field, which can be called critical biography. The most important component of this new style is its connection with the political thought of Islamist parties. As the founder of the Jamaat-e-Islami party, Abul A'la Maududi is considered one of the most important critical biographers of the subcontinent. Therefore, one should ask what is the relationship between the critical biography of the Holy Prophet (PBUH) and Islamic political ideology. The claim, using historical analysis, is that Abul A'la Maududi, using the three components of prophethood, phasing, and anticipating acceptance of the status derived from the life of the Holy Prophet (PBUH), develops the history of human society into an ideological reading. The achievement of Maududi's critique of biography using the three functions of mythmaking, legitimization, and integration provides grounds for consolidating the position of the ideology of political Islam in Pakistan through the application of research conducted.